An Investigation of The Compressive Strength of Cold-formed Steel Built-up I Sections - Lau, Hieng Ho; Ting, T.C.H (The Hong Kong Institute of Steel Construction, 2009)
Cold-formed steel members have been used extensively in low and mid-rise residential building construction. The usage of cold-formed steels as primary structural members has been increased due to its high load to weight ratio. Cold-formed steel built-up sections are commonly used as compression elements to carry larger loads and over longer spans when a single individual section is insufficient. However, not much research has been done on built-up sections. This paper aims to investigate the compressive capacity of pin-ended cold-formed steel built-up I sections using the finite element method (FEM). In the study, cold-formed steel built up I section consists of two identical C-channels sections oriented back to back forming an I-shaped cross section and connected to each other at certain spacing along their length. A non-linear finite element model is developed and verified against theoretical and experimental results. The theoretical numerical analysis is based on the Effective Width Method and the Direct Strength Method. As for the experimental testing, the compression test is carried out on 11 specimens. It was shown that the finite element methods results correlate well with the experimental results. In addition, the analytical results by the Effective Width Method and Direct Strength Method are generally conservative for cold-formed steel built-up I sections.